PENINGKATAN KUALITAS AIR SUNGAI UNTUK IRIGASI PERSAWAHAN PADI DENGAN SISTEM Ã¢â‚¬Å“KONTROL pHÃ¢â‚¬Â DI KABUPATEN BENGKALIS, RIAU - Setiyono, Setiyono; Rahayu, Sri (Jurnal Air Indonesia, 2008)
Bengkalis district has a population of 690,366 people spread in the area of 11,481.77 Km2. Natural resources potencial in this area is quite large, so that local Government has a high commitment to meet the demand of local food, and even regional. To implement this goal, local government will build irrigation systems to irrigate 1,500 ha of rice field land which decrease of water in dry season. However, there are some constraints experienced are : the river for irrigation water source is located near the beach, so it is influenced by tidal sea water. Besides, the peat moss water contains a high organic matter and acid. To solve this problem, we need to treat the river water for irrigation, so that its quality meets the requirement for agriculture. While tidal conditions can be set with the pumping time. From the results of the research in the laboratory showed that the river water pH = 4 while the river water quality standard for the rice field is the appropriate 5 - 9 mg/l. Therefore, the required water treatment to raise pH to comply with the standard quality of water for agriculture. Research conducted in the village Langkat, district Siak Kecil. This activity includes laboratory research, design creation tool to increase pH river water irrigation, tools development, up to the trials and monitoring.Ã‚Â Keywords : Peningkatan Kualitas Air, Irigasi Persawahan, Kontrol pH